Factors That Influence Stock Prices In The Financial Sector On The Indonesian Stock Exchange - Wawan Andang Saputra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Studi Islam Sunan Doe, 2024)
An important element that investors pay attention to before investing is observing the company's stock price. Banking is an industry that plays an important role in contributing to the Indonesian economy. The aim is to determine the correlation of liquidity, solvency, firm size, exchange rates, credit risk and capital with stock prices in banking partially and simultaneously. The independent factors in this research are liquidity which is proxied by the current ratio, solvency is using DER, company size is using the natural logarithm of total assets, the exchange rate is proxied by the middle rate, credit risk is proxied by NPL and capital is proxied by CAR. The dependent factor in this research is the stock price. Research samples were obtained from financial reports listed on the Indonesia Stock Exchange. This research uses quantitative methods, the analysis technique used is descriptive statistics, while the research hypothesis is tested using multiple linear regression analysis with statistical tools. The determination of the sample was carried out using a purposive sampling method in banking. The results of this research show that simultaneously liquidity, solvency, company size, credit risk, exchange rates, and capital can influence bank stock prices. Partially, stock prices are positively correlated with firm size. However, stock prices are still negatively correlated with credit risk as a proxy for NPL. While stock prices have no correlation with liquidity, solvency, exchange rate and capital.